Critical Assessment of Infrastructure Investment Trusts (InvITs) in India and Suggesting measures to increase their Efficiency in comparison with International Instruments - Malav Shah; Kedar Bhagwat (Australasian Accounting, Business and Finance Journal, 2022)
Indian economy, like any other economy, relies heavily on the infrastructure sector. However, by end of 12th five-year plan (2012-2017) private sector investment in infrastructure started declining causing increase in government spending through budgetary support. To boost investment in infrastructure, Securities Exchange Board of India (SEBI) came up with Infrastructure Investment Trust (InvIT) regulations in 2014. InvIT’s are trust holding infrastructure assets that generate steady cash flow with long term concession. The structure of InvIT is similar to Master-Business Trusts instruments that are prevalent in many developed countries like UK, USA, Singapore, Australia & Hong-Kong. They are listed on stock exchange by issuing their units to investors. While interest of investors have increased in recent past, India's progress in InvIT is still at a relatively nascent stage. As on date, around 10 (ten) InvITs are registered with SEBI. In this study we have attempted to do a critical assessment of the market for InvIT in India. We have also evaluated regulations that regulate InvIT in India and compared them with similar International instruments in order to enhance its attractiveness.
Keywords: Infrastructure Investment Trust (InvIT); India; Business Trust; Singapore; Hong-Kong